2012
DOI: 10.1111/j.1438-8677.2012.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and growth acclimation of birch to night temperatures: genotypic similarities and differences

Abstract: The responses of plants to environmental factors are connected to the time of day. In this study, silver birch (Betula pendula) was grown in growth chambers at five different night temperatures (6-22 °C), using gradual changes during the evening and morning hours. Despite the increased night respiration and unaffected daytime net photosynthesis (per square metre), the carbon uptake (biomass) of birch did not decrease, probably due to enhanced biochemical processes on warmer nights and the advantage of higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Martz et al (2010) observed contrasting trends in the most abundant leaf phenolic compounds in V. myrtillus along an elevation gradient: flavonols increased at high elevation, while hydroxycinnamic acids and chlorogenic acid derivatives decreased. In birch leaves, it was also shown that changes in phenolic concentration were partly non‐linear along a temperature gradient (Mäenpää et al 2013). These studies confirm that when observing bulk flavonoids, a hump‐shaped trend would be expected, where some secondary metabolic pathways are limited at low and high altitude and magnified at mid‐high altitude (around 1900 m a.s.l.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martz et al (2010) observed contrasting trends in the most abundant leaf phenolic compounds in V. myrtillus along an elevation gradient: flavonols increased at high elevation, while hydroxycinnamic acids and chlorogenic acid derivatives decreased. In birch leaves, it was also shown that changes in phenolic concentration were partly non‐linear along a temperature gradient (Mäenpää et al 2013). These studies confirm that when observing bulk flavonoids, a hump‐shaped trend would be expected, where some secondary metabolic pathways are limited at low and high altitude and magnified at mid‐high altitude (around 1900 m a.s.l.).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic metabolic paths are expected to be stimulated with increasing elevation (Zou et al 2019). Nonetheless, a consensus on the changing pattern of phenolic compounds with elevation is missing (Rieger et al 2008; Mäenpää et al 2013; Yuliani et al 2019), mainly due to contrasting/inconsistent ( e.g. not linear) trends observed for different families of phenolics (Martz et al 2010) or the often overlooked interactions with other abiotic and biotic factors which co‐vary with elevation ( e.g .…”
Section: Introductionmentioning
confidence: 99%
“…These observations are further supported by climate change scenarios predicting faster increases in T min than T max particularly in mid to high northern latitudes and in arid regions 6 7 . At the same time, a growing body of evidence from long-term observations 8 9 10 11 12 13 , manipulation experiments 14 15 16 17 18 and model simulations 19 20 21 has demonstrated differential impacts of increases in minimum and maximum daily temperatures on plant productivity and terrestrial ecosystems carbon budgets. However, most experiments have been conducted under diurnal constant (symmetric) warming simulations 22 23 , and many models only use daily, monthly, or even annual mean temperatures for the temperature parameterizations when simulating and predicting the responses and feedbacks of terrestrial ecosystems to global warming 24 25 .…”
mentioning
confidence: 99%
“…Improved defence capacity of birch due to warming was demonstrated by higher total antioxidant capacity and redox state of ascorbate (Riikonen et al, 2009). Elevation of night-time temperature in the growth chamber conditions increased the leaf level respiration and shifted the metabolic profiles, depending strongly on the genotypes (Mäenpää et al, 2013). The most clear responses were seen as increased concentrations of triperpenoids, hydrolysable tannins, certain phenolic compounds such as DHPPG (3,4dihydroxypropiophenone-3-ß-D-glucopyranoside) and fructose (Mäenpää et al, 2013).…”
Section: Heating Experimentsmentioning
confidence: 99%